Kolaborasi Guru BK dengan Guru, Orangtua Siswa dan Lembaga Formal di SMP 35 Medan - Hanifatul Muna; Dina Luthfiyyah; Glory Nadine Silalahi (STIKes Ibnu Sina Ajibarang, 2024)
Collaboration between guidance and counseling teachers to overcome student problems is important in efforts to improve students' welfare and learning achievement. This research aims to look at the collaboration carried out by guidance and counseling teachers with subject teachers, homeroom teachers, parents and other professionals. The subject of this research was the guidance and counseling teacher at SMP 35 Medan. Data was collected by teacher bk interviews, observation and documentation. Data analysis is descriptive qualitative. The data that has been collected is then summarized and classified to draw conclusions. The research results show that there is good collaboration between guidance and counseling teachers at SMP 35 Medan with subject teachers and homeroom teachers, students' parents and other professionals such as the police, prosecutor's office and BNN. The collaboration that.